CONVENTION OF THE SETTLEMENT OF INVESTMENT DISPUTES BETWEEN STATES AND NATIONALS OF OTHER STATES (ICSID) - Peruana de Derecho Internacional, Sociedad (2020)
The article explains the operation of the International Center for Settlement ofInvestment Disputes between States and nationals of other States, taking into account theimportance of this center in the resolution of conflicts in Peru today.